Analyzing the effects of minimum wages: a microeconomic approach - Clemens Thielen; Philipp Weinschenk (Economic Theory, 2024)
We use a microeconomic approach to analyze the effects of minimum wages. Agents are allowed to have different productivities at different principals as well as different costs of working. We obtain several new and interesting effects. Minimum wages could influence the generated surplus when leaving employment unaffected, and destroy jobs that generate relatively high levels of surplus when affecting employment. Furthermore, minimum wages could harm agents even if these stay employed, while principals could benefit from them. We provide a complete characterization of the effects and show that these hold independently of the specific bargaining procedure and information structure.
Keywords: C78; D21; J31; J38; K31; 330; Minimum wages; Principal-agent model; Costs of working; Welfare effects